The dynamic ocean acidification manipulation experimental system: Separating carbonate variables and simulating natural variability in laboratory flow‐through experiments. (26th April 2019) - Gimenez, Iria; Waldbusser, George G.; Langdon, Chris J.; Hales, Burke R.
Abstract: Carbonate chemistry variables such as PCO2, pH, and mineral saturation state ( Ω ) are commonly thought of as covarying in open‐ocean settings but have decoupled over geologic time‐scales and among modern dynamic coastal margins and estuaries. Predicting responses of vulnerable coastal organisms to past, present, and future ocean acidification (OA) scenarios requires the empirical identification of organismal sensitivity thresholds to individual carbonate chemistry parameters. Conversely, most OA experiments involve chemistry manipulations that result in covariance of carbonate system variables. We developed the Dynamic Ocean Acidification Manipulation Experimental System (DOAMES)—a feed‐forward, flow‐through carbonate chemistry control system capable of decoupling PCO2, pH, or Ω by independently manipulating total alkalinity (TAlk) and total inorganic carbon (TCO2 ). DOAMES proof‐of‐concept can manipulate source seawater with stable or variable carbonate chemistry and produce experimental treatments with constant and dynamic carbonate chemistry regimes. The combination of dynamic input and output allows for offset treatments that impose a ΔPCO2 on naturally variable conditions. After overcoming several operational challenges, DOAMES is capable of simultaneously generating three different experimental treatments within 1% ± 1% of TCO2 and TAlk targets. The achieved precision and accuracy resulted in the successful decoupling of pH and Ω Ar in five trials. We tested the viability of sensitive bivalve embryos raised in DOAMES‐manipulated seawater and found no difference in development when compared to the control, demonstrating DOAMES suitability for organismal studies. DOAMES provides a novel tool to evaluate organismal effects of exposure to decoupled carbonate system variables and to past, current, and future carbonate chemistry scenarios.